Cultural Socialization in Transracial Adoption: Adoption Support, Multicultural Experiences, Perceptions of Discrimination, and Positive Feelings Toward Racial Minority Groups. Issue 4 (2nd October 2019) - Heiden-Rootes, Katie; Miller, Bobbi; Moore, Rachel
Abstract: The current study compared transracial adoption (TRA) parents who adopted internationally to those who adopted domestically (total n  = 188; domestic n  = 71; international n  = 117) on multicultural experiences, perception of discrimination, and positive feelings toward racial minority groups, adoption support, and Parental Cultural Competence (PCC). Next a model for predicting PCC for both groups was tested. Results indicated significant differences between the groups based on multicultural experiences, perception of discrimination and positive feelings towards racial minority groups, and degree of available adoption support. Regression models predicting PCC tested with groups combined and separate suggest the significant role of multicultural experiences in predicting PCC for both groups; however, the largest effect of multicultural experiences on PCC was seen for domestic transracially adoptive parents. Discussion of results is considered with implications for future research.